2012
DOI: 10.1007/s12020-012-9842-5
|View full text |Cite
|
Sign up to set email alerts
|

Is autoimmune thyroiditis a risk factor for early atherosclerosis in premenopausal women even if in euthyroid status?

Abstract: Autoimmune thyroiditis (AIT) is a systemic disease. It is well-known that overt thyroid dysfunction is a cardiovascular risk factor. However, the influence of euthyroid status is unclear. The aim of this study was to evaluate the metabolic parameters and carotid intima-media thickness (CIMT) in euthyroid premenopausal women with AIT. Fourty-eight premenopausal women and 18 age-matched healthy controls attending the Endocrinology and Metabolism Clinic from 2008 to 2009 were enrolled to this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
7
34
0
Order By: Relevance
“…Our results were partially in line with Tamer et al [35] who have concluded that the thyroid autoimmunity disorder can be proved to be correlated with hyperlipidemia and atherosclerosis, independent of the thyroid function. According to the study, the serum level of TPO Abs bears a negative relationship with HDL; which is confirmed in another study where a positive correlation between Anti-TPO Abs and cholesterol and LDL is also reported [36]. …”
Section: Discussionsupporting
confidence: 64%
“…Our results were partially in line with Tamer et al [35] who have concluded that the thyroid autoimmunity disorder can be proved to be correlated with hyperlipidemia and atherosclerosis, independent of the thyroid function. According to the study, the serum level of TPO Abs bears a negative relationship with HDL; which is confirmed in another study where a positive correlation between Anti-TPO Abs and cholesterol and LDL is also reported [36]. …”
Section: Discussionsupporting
confidence: 64%
“…It is, therefore, imperative that future high-quality evidence confirms or refutes that autoimmune thyroid disease is a risk factor for atherosclerosis. The current report by Topaloglu et al [14] reinforces this need.…”
supporting
confidence: 69%
“…In this issue of Endocrine, Topaloglu et al [14] add further evidence to the debate. This study recruited 48 euthyroid premenopaual women with Hashimoto's thyroiditis and compared them to 18 controls with respect to CIMT, cardiovascular risk factors, and metabolic parameters.…”
mentioning
confidence: 98%
“…Currently, however, the causative relationship between thyroid autoimmunity and increased risk of atherosclerosis has not yet been established. A few studies which were addressing this question investigated the effect of thyroid autoimmunity on lipid profile, abdominal obesity, fasting glucose and homeostasis model assessment (HOMA) insulin resistance, as well as carotid intima-media thickness (CIMT) [25][26][27]. However, in contrast to our study group, the study populations were not uniform, therefore the conclusions of these investigations are not comparable.…”
Section: Discussionmentioning
confidence: 79%